Evaluation of the content validity of the intrinsic-instrumental assessment tool for assessing the nature values of constructed wetlands - Nurul’ Ain Jamion,; Lee, Khai Ern; Mazlin Mokhtar,; Goh, Thian Lai; Norbert Simon, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Constructed wetlands possess tremendous nature values, namely instrumental and intrinsic values. Constructed wetlands also store and capture carbon which help to mitigate climate change in sustaining our earth system. Hence, sound management of constructed wetlands must consider its importance as essential assets that increase their resilience in mitigation and adaptation strategies towards adverse effects of climate change. To examine the vital value of constructed wetlands, this study attempts to evaluate the content validity of the developed Intrinsic-Instrument Assessment (IIA) tool for assessing the nature values of constructed wetlands in the context of climate change. A methodological study was conducted to evaluate the content validity of the IIA tool in two-phases. First, a comprehensive literature review was conducted at the development phase to identify the construct and dimension, generate items and instrument formation. In the second phase (evaluation), a committee of six experts performed the content validity evaluation, and the content validity index was implemented for content validity quantification. Finally, the researcher conducted a discussion between the team members to finalise the items of the IIA tool. The first version of the IIA tool identified three domains (instrumental, objective and intrinsic values) with 36 items. The item content validity index (I-CVI) ranges from 0.833 to 1. The overall content validity index using the average approach, the scale content validity index (S-CVI/Ave) is 0.97. Thus, the IIA tool was evaluated with highly relevant and excellent content validity. Researchers generated 17 additional items in the IIA version 2.0 after considering experts’ feedback. Still, after the second evaluation by researchers, the final version of the IIA tool consists of 42 items. This paper contributes to the body of knowledge by performing the systematic process of the essential steps to verify the developed instrument’s reliability and validity, especially in the field of socio-ecology. This study provides comprehensive information and example as guidance for evaluating content validity for a new instrument scale. Also, it helps to bring insight into constructed wetlands’ vital nature values as the nature solution in mitigating and adapting climate change to advocate the sustainable development of constructed wetlands ecosystems.